PEMBERIAN PUPUK ORGANIK CAIR DAUN GAMAL (POC) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KAILAN (Brassica oleracea var. Acephala) - Devita G. Lontoh; Jeanne M. Paulus; Beatrix Doodoh; Johannes E.X. Rogi; Saartje Sompotan; Sesilia A. Wanget (Universitas Sam Ratulangi, 2024)
This research aims to determine the effect of applying liquid organic fertilizer from gamal leaves on the growth and yield of kailan plants, as well as the best concentration of using liquid organic fertilizer from gamal leaves. This research was carried out for three months, from June to September 2023 in Wailan Village, Tomohon City, North Sulawesi. This research design used a Randomized Block Design with 5 concentrations of liquid organic fertilizer consisting of P0 (POC 0 ml/L water), P1 (POC 50 ml/L water), P2 (POC 100 ml/L water), P3 (POC 150 ml/L water), P4 (POC 200 ml/L water) and all treatments were repeated three times until there were 15 plots. The variables observed were plant height (cm), number of leaves (pieces), leaf width (cm), plant wet weight (g). The data analysis method used is analysis of variance (ANOVA) and if it has a real effect it will be continued with the LSD test at the 5% level. The results of the research showed that giving Gamal leaf Liquid Organic Fertilizer (POC) had an effect on the growth of plant height, number of leaves and wet weight of kailan plants, and the best giving Gamal leaf POC was at a concentration of 200 ml/L water. Keywords : liquid organic fertilizer, gamal leaves, kailan